2022
DOI: 10.33545/26164485.2022.v6.i4f.683
|View full text |Cite
|
Sign up to set email alerts
|

A case of wrist ganglion treated with individualized homoeopathic medicine: A case report

Abstract: Ganglion are benign cystic swelling of unknown aetiology that most commonly encountered in the wrist especially dorsal aspect. Women are more frequently affected especially between age of 20-50 years. Although these are asymptomatic but may present with symptoms include wrist pain especially with movement or when a mass is felt, a reduction in range of motion, and a decrease of grip strength. Clinical presentation is usually sufficient for its diagnosis. A case of 25-year-old female suffering from wrist gangli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…After extensive searches into different electronic (PubMed, CORE Hom, Embase, etc.) and bibliographic databases, very few numbers of studies were identified evaluating homoeopathy in wrist ganglion (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…After extensive searches into different electronic (PubMed, CORE Hom, Embase, etc.) and bibliographic databases, very few numbers of studies were identified evaluating homoeopathy in wrist ganglion (6,7).…”
Section: Introductionmentioning
confidence: 99%